Icaritin inhibits the invasion and epithelial‐to‐mesenchymal transition of glioblastoma cells by targeting EMMPRIN via PTEN/AKt/HIF‐1α signalling. (December 2015) - Xu, Bo; Jiang, Chuanwu; Han, Hongxing; Liu, Hong; Tang, Ming; Liu, Longxi; Ji, Wenyan; Lu, Xuechao; Yang, Xiuli; Zhang, Yunxu; Liu, Yongji
Summary: Icaritin, a hydrolytic product of icariin from the Epimedium genus, exerts anti‐tumour effects on a variety of tumour cell types, mainly by inhibiting cell proliferation and inducing apoptosis. However, little is known about the role of icaritin in cancer invasion and epithelial‐to‐mesenchymal transition (EMT). In the present study, the glioblastoma (GBM) cell line U87MG was used as a model to investigate the effects of icaritin on the invasion and EMT of cancer cells. The results showed that icaritin significantly inhibited the invasion and EMT of GBM cells by targeting extracellular matrix metalloproteinase (EMMPRIN). Furthermore, the findings strongly indicate that the modulatory effect of icaritin on EMMPRIN is mediated via the PTEN/Akt/HIF‐1 α signalling pathway. The data provide the first experimental evidence of the inhibitory effect of icaritin on cancer cell invasion and EMT, thus highlighting the potential of icaritin to be employed as a promising anti‐cancer agent in the treatment of GBM.